Pengaruh Kepuasan Kerja dan Kedisiplinan Kerja Terhadap Kinerja Karyawan pada PT. Macroprima Panganutama - Indah Anggraeni Purnama Sari; Raka Kusuma Nugraha; Juharna; Iin Marneti; Karnawi Kamar (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to determine: (1) The partial effect of Job Satisfaction on Employee Performance (2) Work Discipline partially on Employee Performance (3) The simultaneous effect of Job Satisfaction and Work Discipline on Employee Performance This study is an associative study. The population in this study were 92 employees of PT. Macroprima Panganutama. The sampling technique used Probability Sampling, Sample Random Sampling category, the data used in this study were primary data, namely data obtained from questionnaires, in this study the data analysis was carried out using SPSS version 18.00, with validity test data, reliability test, Descriptive Statistics Test and then valid and reliable data were then carried out classical assumption tests, correlation tests, regression tests, coefficient of determination tests, hypothesis tests namely f tests and t tests to find out answers to research problems through the collected research data. The results of this study indicate a coefficient of determination (R) of 83.0%. This indicates that job satisfaction and work discipline influence employee performance by 83.0%, with the remaining 17% influenced by other factors. The calculation of the hypothesis Fh yielded a value of 217.489 > f table 2.36, therefore, Ha is accepted, Ho is rejected. The results of the multiple linear regression between employee performance variables are Y = 3.189 + 0.536X₁ + 0.470X2. It can be seen that job satisfaction has a partial positive effect on employee performance at PT. Macroprima Panganutama, and work discipline has a partial positive effect on employee performance at PT. Macroprima Panganutama. Simultaneously, job satisfaction and work discipline have a significant effect on employee performance at PT. Macroprima Panganutama.